Nature and the grotesque in Tunku Halim’s dark demon rising and Juriah’s song - Ahmad Jafni, Nur Fatin Syuhada (2015)
Horror novels often celebrate gore, darkness, madness and emotional repression as the central themes to invoke terror and horror in readers. In novels written by Malaysian author Tunku Halim, Dark Demon Rising (1997) and Juriah’s Song (2008) the elements of grotesque and nature provide the impetus and the plot, thus invoking horror. Throughout both novels, grotesque elements and imagery are woven into narrative to provide the motif of horror. Apart from the evident elements of grotesque, nature as a backdrop is also significant, as both novels are set in rural villages in the east coast of Malaysia and the metropolis of Kuala Lumpur. The grotesque and nature are juxtaposed as main elements in these novels. Both elements are omnipresent and pivotal in developing the plot. Noting the relationship between the two elements, this research first highlight the relationship between the grotesque and nature as an aesthetical mode in the selected novels; and secondly, explore the relationship between the grotesque and nature through the portrayal of the human-nature interconnectedness in the selected novels. This research applies the concepts of ecocriticism and grotesque. Ecocriticism provides sufficient explanation on the relationship between human and the natural world. The concept of grotesque by Wolfgang Kayser provides a solid framework in highlighting and exploring the texts. The application of these concepts will then demonstrate that apart from imagery, the role of nature is also evident in the relationship between human and nature. With the establishment of the grotesque and nature as an aesthetical mode, the relationship between the two is depicted through Kayser’s notion of the grotesque as a creative process. It has been revealed that the aesthetical grotesque is portrayed through the monstrous form and the transgression and disharmony. Apart from that, the interrelationship between nature and the grotesque is also portrayed under Kayser’s notion of the grotesque reception. Pertaining to this notion, the interconnectedness is unveiled through the comic/horror and attractive/repulsive dualities. The finding concludes that the element of nature depicts the grotesque process and reception via the characters’ demeanor, especially the protagonists’ emotions, perceptions and attitude.